Reforming “Merariq”: Towards Harmonized Approach – Socio-culture, Islamic Law, and Biological Consequences - Toetik Koesbardiati; Sri Endah Kinasih; Mochamad Kevin Romadhona; Rachmah Ida; Irfan Wahyudi (Journal of Law and Legal Reform, 2025)
Research Objectiveness: The understanding of marriage is the process of binding, both physically and spiritually, between a man and a woman to become husband and wife aimed at forming a lasting, harmonious, and happy family based on the belief, this research aims to identify and analysis merariq culture in the aspects of socio-culture, legal, and health. Methods: This research is qualitative research using descriptive analysis. Qualitative study aims to explore the endogamous marriages in Mungkik, Pandan Wangi Village, Jerowaru Subdistrict, East Lombok, involved 24 women and girl (married, unmarried, and widower). Research findings: East Lombok's marriages are primarily merariq, a deeply ingrained tradition in the Sasak community. Elopement often arranged by parents, demonstrating bravery and maintaining family relationships. However, endogamous marriages in Merariq families can lead to health issues and genetic disorders. Among them, 75% of participants were admitted to endogamous marriages among relatives, and some parents forbid their children from marrying relatives due to guilt. Merariq marriages are decreasing due to the rupture of family ties. Elopement is a traditional rational action, low-risk, and based on customs and traditions. However, the community is unaware of the health risks and lacks prior socialization.